Pengaruh Tekanan Kerja, Komitmen Kerja dan Motivasi Terhadap Kinerja Sub PPKBD di Kecamatan Gombong - Siti Nur Azizah; Blandina Kriswi Anggraeni (Universitas Peradaban, 2017)
The purpose of this study was to determine the effect of work pressure, work commitment and motivation on the performance of Sub PPKBD in UPT BPPKB Kecamatan Gombong. Variables in this study consist of two types of independent variables that include work pressure, work commitment, and motivation. While the dependent variable includes performance. The population in this study were all Sub PPKBD in UPT BPPKB, totaling 87 people. Respondents were drawn as many as 87 people, so all members of the population sampled (study population). The research method is quantitative analysis and the data then be analyzed by the statistical technique of multiple linear regression analysis. The result of this research indicate that the variables work pressure, work commitment and motivation give positive and significant influence to performance either partially or simultaneously. Later analysis of the coefficient of determination (Adjusted R Square) work pressure (X1), work commitment (X2) and motivation (X3) effect by 42,3% to variable performance (Y), while the remaining 57,7% is explained by other factors outside the model.